Menciptakan Lapangan Kerja Bagi Fresh Graduate Melalui Program Workshop Dan Seminar Move On Entrepreneur - Alfatih S. Manggabarani; Nunuk Triwahyuningtyas (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2019)
Through this service, we hope to empower the optimal candidates, so that new graduates can take part in Smart Jurus Seminars and Workshops Gaining Business Wealth. "MOVING SEMINARS AND WORKSHOPS IN ENTREPRENEURS. To Get Profit Through Business. Why If You Want To Be Successful and Rich You Must Be An Entrepreneur? "This is one way to share entrepreneurial knowledge with alumni, especially the younger generation, so that someday they can become strong and successful entrepreneurs in the future. The workshop participants were 100 new graduates in 2017/2018 before the graduation ceremony.